Pengembangan aplikasi E-UKBM kimia sebagai media pembelajaran interaktif siswa kelas XI SMAN Bali Mandara - I Wayan Madiya (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2020)
This research is motivated by a lot of students who miss the subject matter, e-UKBM learning has not run effectively, the demands of e-UKBM assignments are many and HOTS, the completion time is long, and students prefer to play with friends, laptops/smartphones. The purpose of this study is to analyze (1) the chemical e-UKBM application functionality, (2) application eligibility, (3) application performance at different resolutions; and (4) the effectiveness of applications as interactive learning media. This research is an R&D research model of ADDIE which was conducted at the SMAN Bali Mandara from January-October 2019 with 27 subjects of class XI MIPA1 as the trial subjects. Product feasibility test is validated by material and media experts, alpha test, and beta test. Data collected using observation, interviews, questionnaires, and post-test were analyzed usingdescriptive analysis. The results show that (1) the chemical e-UKBM application functionality test includes ease of navigation, application performance, and operational functioning very well; (2) the feasibility of the application is based on the assessment: material experts, media experts, teachers, and students respectively are 89%, 89%, 92%, and 95% with the category